2018
DOI: 10.1177/1847979018773260
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the integrated production and maintenance planning using genetic algorithm

Abstract: In spite of the interdependence between them, production and maintenance planning decisions are generally studied and used independently in the majority of the manufacturing systems. Our contribution is summarized to obtain a maintenance policy including preventive replacement in each maintenance cycle and minimal repair in case of unplanned failure, and on the other side, for a set of products and in each period, specify the quantity to be produced and when is the production set up, also the stock and the bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Most of these combinations are either in a linear form or in a distance derivative. 33,34 Some of the relevant methods for solving optimization problems are weighted aggregation, global criteria, minimum deviation, and compromise programming. The latter is adopted in this study.…”
Section: Multiple Objective Formulation For Simultaneous Optimizationmentioning
confidence: 99%
“…Most of these combinations are either in a linear form or in a distance derivative. 33,34 Some of the relevant methods for solving optimization problems are weighted aggregation, global criteria, minimum deviation, and compromise programming. The latter is adopted in this study.…”
Section: Multiple Objective Formulation For Simultaneous Optimizationmentioning
confidence: 99%
“…It has been reported that most integrated production and maintenance scheduling problems, with availability constraints, under different machine configurations and various objective functions are NP-hard problems (Kubiak et al, 2002). Because of this restraining feature, various heuristic and metaheuristic algorithms such as Genetic Algorithms (GA) and Simulated Annealing (SA) have been employed to tackle these problems (Aggoune and Portmann, 2006;Wang, 2013;Zhao et al, 2014;Ettaye et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2 Many researchers studied different settings and extensions of this classical problem. These include, but are not limited to, integrated models, 3 bundling strategies, 4 variable lead-time, 5 variable production rate, 6 and variable holding cost. 7 Several survey papers can be found on this problem and its variations, as examples: Glock,8 Ramasesh, 9 Drexl and Kimms, 10 and Zoller and Robrade.…”
Section: Introductionmentioning
confidence: 99%